Dietary aluminium intake disrupts the overall structure of gut microbiota in Wistar rats. Issue 11 (20th June 2022) - Wang, Bo; Wu, Caihong; Cui, Lianzhi; Wang, Hui; Liu, Ya; Cui, Weiwei
Abstract: Approximately, 40% of ingested dietary aluminium accumulates in the intestine, which has been considered a target organ for dietary aluminium exposure. The gut microbiota may be the first protective barrier against the toxic metal aluminium and a crucial mediator of the bioavailability of metal aluminium. We previously evaluated dietary aluminium intake and its health risks in a population from Jilin Province, China, and found that the average daily intake of aluminium in the diet of residents in Jilin Province was 0.163 mg/kg after the total diet survey. In the present study, the equivalent concentration of aluminium in rats was extrapolated by the average dietary aluminium intake in the population of Jilin Province based on body surface area. Furthermore, healthy adult Wistar rats were randomly divided into four groups ( n  = 15 for each group): a control group and three groups treated with aluminium solution (1, 10, and 100 mg/kg/day, intragastrically) for 28 days. Following treatment, necrosis of renal tubular epithelial cells, hyperplasia of bile ducts and hyperplasia of heart tissue, as well as fiber in the liver, kidney, and heart tissues of aluminium‐treated rats were observed, although there were no significant changes in the spleen and brain. Subsequently, fecal samples were withdrawn for 16S rRNA gene sequence analysis. It was found that aluminium decreased the microbiota diversity and changed the overall community structure of the gut microbiota, including three phyla and four genera, together with the regulation of 12 signaling pathways. Collectively, treatment with aluminium markedly altered the structure of the gut microbiota, suggesting that the disorders of intestinal flora induced by aluminium may be an important mechanism for aluminium toxicity. Abstract : Aluminium could decrease the microbiota diversity, change the overall structure of the gut microbiota, including three phyla and four genera, together with regulations of 12 signalling pathways. Treatment with aluminium markedly altered the structure of the gut microbiota, suggesting that the disorders of intestinal flora induced by aluminium may be an important mechanism for aluminum toxicity. It also further reminds people to reduce the use of aluminium‐containing food additives during food processing or replace them with other alternatives as far as possible, and protects people's health by maintaining the homeostasis of intestinal flora through a healthy diet.